Serum N-Terminal Pro-Brain Natriuretic Peptide, D-Dimer Levels In Community-Acquired Pneumonia and Its Correlation with CURB-65 as a Prognostic Marker - Dr.Kuppani Dinesh; Dr.Uma.M.Anand Kumar2; Dr. Mythreini B S; Dr Jagadish K L; Dr Modapalli Lohith Chowdary (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Community-acquired pneumonia (CAP) is a common medical condition, especially in older adults, and is usually associated to systemic inflammatory response syndrome (SIRS). The study aimed to study serum N-terminal pro-brain natriuretic peptide (NT -probnp) and D-dimer levels in community acquired pneumonia and its correlation with CURB-65 as a prognostic marker. Methods: A prospective study was conducted for 18 Months among 96 patients admitted with community-acquired pneumonia. All eligible patients underwent relevant investigations like renal function tests, liver functions tests, complete blood count, blood –culture and sensitivity, sputum or tracheal aspirate – gram stain, culture and sensitivity, ECG, Chest X ray, USG abdomen. The scoring will be done in these patients to assess the severity and the need for admission in these patients including CURB 65 and PSI. Results: Among 96 patients, Comorbidities are present in 67% of the study population. The mean and SD NT pro-BNP levels are 336.58±109.78pg/ml. Survivors’ mean NT-proBNP levels were 321.37 pg/ml. 425.71 pg/ml with an SD of 108.74 pg/ml are found in non-survivors. Survivors have mean D-dimer levels of 1410.39 ng/ml, while non-survivors have mean D-dimer levels of 2334.29 ng/ml with SD of 1173.00 ng/ml. Conclusions: The values of NT proBNP and D-dimer in the survivors of patients with higher CURB-65 are lower in this study and in non survivors even with a lower CURB-65 the values of D-dimer and NT pro BNP are higher indicating that NT pro BNP and D-dimer levels are slightly better in predicting the mortality and prognosis which is statistically significant.